Penerapan Program Tahfidzul Qur’an Di SMP Islamic Center Samarinda - Achmad Ruslan Afendi; Alpin Dianto; Lucky Purnama Sultan; Miftahul Hidayah (Ta'limDiniyah: Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2023)
This research has the aim of examining a good program at the Samarinda Islamic Center Middle School in the form of the tahfidzul Qur'an program, which with this program is expected to be able to overcome the problems faced by students such as difficulties in understanding and remembering subject matter, because the tahfidz program can helps improve concentration, thinking ability, strengthens thinking power and memory which aims to increase student understanding during learning, which is certain if students' understanding of the subject matter increases it will have an impact on the grades or learning outcomes of students who are progressing especially in PAI subjects.